Carrier-free delivery of nucleic acid and photosensitizer nanoparticles for enhanced photodynamic and gene antitumour therapy - Ningyu Li; Fan Dong; Lisha Sun; Yuping Qian; Ludan Zhang; Guiyan Wang; Lintian Yuan; Hong Liu; Yong Jiang; Yuguang Wang (Fundamental Research)
Activated anti-oxidation reactions in cells partially diminish the anticancer effect of photodynamic therapy (PDT), significantly hindering efforts to increase the efficacy of PDT. The expression of transcription factor E2 related factor 2 (Nrf2), an important redox-regulated transcription factor, can be downregulated by Nrf2 siRNA, leading to greatly enhanced PDT effects. However, the efficient co-delivery of photosensitizers and siRNAs remains a key problem because these agents are complex to synthesize, exhibit poor biocompatibility and load drugs with a low efficiency. Herein, we designed a carrier–free and extremely simple strategy to co-deliver a photosensitizer and Nrf2 siRNA to cancer cells. In this nanoplatform, an indocyanine green photosensitizer, siRNA and FeⅡ were self-assembled to form a spherical hybrid structure with a uniform size, high loading ratio and adjustable component ratio. The platform can effectively transfer photosensitizers and siRNAs into cells and effectively inhibit tumour growth in vivo. Overall, the self-assembly approach shows great potential for clinical application and provides a simple method to achieve photodynamic therapy and enhanced photothermal therapy.